2012
DOI: 10.1084/jem.20120565
|View full text |Cite
|
Sign up to set email alerts
|

RAE-1 ligands for the NKG2D receptor are regulated by E2F transcription factors, which control cell cycle entry

Abstract: E2F transcription factors regulate expression of RAE-1 family NKG2D ligands in cancer cells and normal proliferating cells to promote wound healing and immune recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(130 citation statements)
references
References 47 publications
5
123
0
Order By: Relevance
“…They are consistent with previous evidence showing that E2F1 transcription factor is responsible for the transcriptional regulation of MICA and PVR in a manner dependent on ROS-induced DDR signaling and p53 independent, and of the mouse NKG2D ligand Rae-1 in response to proliferative signals ( 14,44 ). As far as ULBP1, this kinase affects the protein cellular distribution, but not gene transcription.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They are consistent with previous evidence showing that E2F1 transcription factor is responsible for the transcriptional regulation of MICA and PVR in a manner dependent on ROS-induced DDR signaling and p53 independent, and of the mouse NKG2D ligand Rae-1 in response to proliferative signals ( 14,44 ). As far as ULBP1, this kinase affects the protein cellular distribution, but not gene transcription.…”
Section: Discussionsupporting
confidence: 93%
“…p38 MAPK controls MICA and PVR ligand upregulation on drug-treated MM cells through activation of E2F1 transcription factor E2F1 transcription factor is responsible for the transcriptional regulation of NKG2D and DNAM-1 ligand in cells undergoing proliferation or genotoxic stress ( 14,36 ). This transcription factor can be activated in response to different signaling pathway(s), and is stabilized by specific phosphorylation at Ser364, by the Chk2 or p38 kinase ( 37,38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these results reveal the importance of E2F1 in the regulation of human NKG2D and DNAM-1 ligands in response to ROS-dependent, drug-induced genotoxic stress and suggest a more general role of the E2F family transcription factors recently implicated in the control of mouse Raet1 genes in proliferating fibroblasts (56).…”
Section: Discussionmentioning
confidence: 65%
“…NK cells recognize mouse cancer cells via ribonucleic acid export-1 (RAE-1) family ligands and human cancer via MHC class I-related genes A and B (MICA and MICB), all of which bind the NK cell-activating receptor NKG2D (84,87,88). These NKG2D ligands are upregulated during the DNA damage response and cell cycle progression via E2F transcription factors (89). The antitumor activity of NK cells was mainly observed in hematopoietic malignancies, but it was recently shown that in mice, MULT1, a high-affinity NKG2D ligand that is released by cancer cells, causes NK cell activation and rejection of solid tumors (90).…”
Section: The Good: Immunity and Cancermentioning
confidence: 99%